EFFECT OF THE DEVELOPMENT LEVEL OF THE URBAN PLANNING ENVIRONMENT ON THE URBANISED TERRITORIES OF THE ASTRAKHAN REGION - N. V. Kupchikova; M. N. Nikolaenko; T. Yu. Ovsiannikova (Вестник Дагестанского государственного технического университета: Технические науки)
Objectives The aim of the study is to assess the level of development of the urban planning environment in the urbanised areas of the Astrakhan region and to determine the priority areas of the construction complex on the basis of the data obtained.Methods The evaluation of development indicators for the urban planning environment is based on the methods of economic-statistical and comparative analysis as well as the index method.Results Based on the proposed methodology, a calculation of the development indices of the urban planning environment of the cities of the Astrakhan region is carried out. Priority directions of investment and development of urbanised territories are identified.Conclusion The methodology for assessing urban planning development allows the activities of the construction complex to be targeted towards an improvement of the urban planning environment. The article presents the results of assessing the development level of the urban planning environment in the urbanised areas of the Astrakhan region. Based on this assessment, priority directions of the construction complex activities are determined and some results of interregional research are presented.